Design of a couse methodology for analysis of public policy development: the productive local arrangements in question - Wolff, Simone; Silva, Cinthia Xavier da; Ferreira, Leonardo Antonio Silvano (Universidade Estadual de Campinas, UNICAMP, Unidade da Faculdade de Ciências Aplicadas de Limeira-SP, vinculada ao Laboratório de Estudos do Setor Público, LESP, 2013)
Local Productive Arrangements are part of a public policy proposal which focuses on the "local development", displayed as a form of development which is able to equate the vulnerabilities of companies and regional and local job markets in view of the trans-nationalization of capital, and its tendency to weakening formal employment. We intend to design a preliminary methodological course in order to provide parameters for analyses which aim at assessing to what extent such policy is successful. Conversely to the official perspective, this methodology suggests that such arrangements tend to reinforce the tendency to deregulating work relations, which are engrossed in productive chains of large corporations, favoring their headquarters in detriment of valuing the employment formally protected, and its social benefits. In order to do that, the Local Productive Arrangement – LPA of the clothing sector in Londrina-PR and adjacent regions - will be taken as the object of analysis.